PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DENGAN MEDIASI KOMITMEN ORGANISASIONAL (Studi Pada SMPN Se-Kecamatan Kesesi Pekalongan) - Ahmad Tasdikin, 12.52.02.0041; Susilowati, Yeye (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to analyze the influence of organizational culture and leadership style on teacher performance with mediation of organizational commitment (Study on a SMP districts kesesi pekalongan). The method used in this study is the method of census the number of 99 respondents. Testing in this study use the instrument test, normality test, the classical assumption, test models, test hypotheses and test mediation effects. Test instruments used in this study is to test the validity of the KMO > 0.5 and Loading Factor > 0.4 and reliability tests with Cronbach alpha > 0.7. Test classical assumptions used were: test heteroscedasticity and multicollinearity test while the test models used are Test Adj R2 (coefficient of determination) and F Test (Goodness of Fit). Hypothesis test used in this study is a regression analysis using the t test , hypothesis testing used standardized beta coefficient and significance level of <0.05.While testing mediation effects by using path analysis path. The findings of the study are as follows : Leadership Style has a positive and significant impact on Organizational Commitment, Organizational Culture has a positive and significant impact on Organizational Commitment, Leadership Style has a positive and significant impact on teacher performance, organizational culture has a positive and significant impact on teacher performance, Organizational Commitment has a positive and significant impact on teacher performance, Organizational commitment mediates the effect of Leadership Style on Teacher Performanc, Organizational Commitment mediates the influence of organizational culture on teacher performance. Keywords: Leadership Style, Organizational Culture, Organizational Commitment and Performance teacher.